The Influence Of The Community And Village Empowerment Office (Dpmg) On Infrastructure Development (Case Study In Krueng Ceuko Village, Seunagan Sub-District, Nagan Raya District) - Fazliadi, Bismi; Sani, Sri Rosmiati; Shifa, Mutiara (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research aims to determine the influence of the Community and Gampong Empowerment Service (DPMG) on Social Services, Development of Social Facilities and Development of Environmental Infrastructure in Krueng Ceuko Village, Seunagan District, Nagan Raya Regency. The data used in this research comes from secondary data obtained from the Central Statistics Agency (BPS) of Nagan Raya Regency. Then, to complete and support this research, the author also used library research and internet sources. The variables used are the Role of DPMG (Y) and Social Services, Development of Social Facilities and Development of Environmental Infrastructure as (X). The results of the research show that the Social Service Variable has a significant and partial positive effect on the Role of the Community and Gampong Empowerment Service (DPMG) in Case Study Infrastructure Development in Krueng Ceuko Village, Seunagan District, Nagan Raya Regency with a standard error of 0.046. The Social Facilities Development variable has a significant partial positive effect on the role of the Community and Gampong Empowerment Service (DPMG) in Infrastructure Development Case Study in Krueng Ceuko Village, Seunagan District, Nagan Raya Regency with a standard error of 0.235, the Environmental Infrastructure Development Variable has a significant partial positive effect on The Role of the Community and Gampong Empowerment Service (DPMG) in Infrastructure Development, Case Study in Krueng Ceuko Village, Seunagan District, Nagan Raya Regency with a standard error of 0.231. The variables Social Services, Development of Social Facilities and Development of Environmental Infrastructure simultaneously have a positive and significant effect in increasing the role of DPMG in Nagan Raya Regency.